Characterizing individual differences in children and adolescents with autism spectrum disorder: a descriptive study - Di Vara, S.; Guerrera, S.; Menghini, D.; Scibelli, F.; Lupi, E.; Valeri, G.; Vicari, S. (Frontiers in Psychology, 2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by a higher prevalence in males than in females. Recent studies have hypothesized the presence of different phenotypes in males and females with ASD. The present study aims to assess possible sex differences in cognitive and adaptive functioning, symptomatology of ASD, and psychopathological comorbidities in a large sample of children and adolescents with ASD.The study included a total of 2146 children and adolescents diagnosed with ASD, comprising 1785 males (mean age 7.12 ± 3.69 years) and 361 females (mean age 6.25 ± 3.30 years). The age of the participants ranged from 1.35 to 19.05 years (mean age 9.98 ± 3.64). The study sought to include all children and adolescents diagnosed with Autism, Asperger's, Pervasive Developmental Disorder -Not Otherwise Specified, or ASD.Present results showed that females with ASD had lower IQ than males, but similar adaptive functioning. The severity of symptoms of ASD was greater in males than in females, as were scores on psychopathological measures. With increasing age, boys with ASD showed greater impairment in social communication skills than females and increased psychopathological comorbidities. Older girls showed fewer restricted and repetitive behaviors.Exploring phenotypic differences in children and adolescents with ASD fosters understanding of subtle diagnostic facets that may go unrecognized, allowing for increasingly individualized and tailored interventions. systematic review and meta-analysis conducted in the United Kingdom (Loomes et al., 2017) as well as recent American data, which estimated a 3.8-fold higher prevalence among males than females and a prevalence estimate of ASD per 1,000 children aged 8 years was 27.6 (Maenner et al., 2023).